Clinician Knowledge, Attitudes, and Practice Regarding Cannabis: Results from a National Veterans Health Administration Survey. Issue 11 (7th January 2020) - Kansagara, Devan; Morasco, Benjamin J; Iacocca, Megan O; Bair, Matthew J; Hooker, Elizabeth R; Becker, William C
Abstract: Background: Cannabis is increasingly available and used for medical and recreational purposes, but few studies have assessed provider knowledge, attitudes, and practice regarding cannabis. Methods: We administered a 47-item electronic survey to assess nationwide Veterans Health Administration (VHA) clinician knowledge, beliefs, attitudes, and practice regarding patients' use of cannabis. Results: We received 249 completed surveys from 39 states and the District of Columbia. Fifty-five percent of respondents were female, 74% were white, and the mean age was 50 years. There were knowledge gaps among a substantial minority of respondents in specific areas: terminology, psychoactive effects of cannabis components, VHA policy, and evidence regarding benefits and harms of cannabis. Most respondents were likely or very likely to plan to taper opioids if urine drug testing was positive for tetra-hydro cannabinol (THC; 73%). A significantly greater proportion of respondents from states in which cannabis is illegal for any purpose (odds ratio [OR] = 4.9, 95% confidence interval [CI] = 2.0–10.8) or is recreationally illegal (OR = 5.0, 95% CI = 2.4–10.8) reported being likely or very likely to taper opioids as compared with respondents from states in which cannabis is legal for medical and recreational purposes. Conclusions: Among the sample, we found knowledge gaps, areas of discomfort discussing key aspects of cannabis use with their patients, and variation in practice regarding opioids in patients also using THC. These results suggest a need for more widespread clinician education about cannabis, as well as an opportunity to develop more robust guidance and evidence regarding management of patients using prescription opioids and cannabis concomitantly.